Comparable assessment of adolescent repeated physical or psychological stress effects on adult cardiac performance in female rats - Monireh-Sadat Mousavi; Sogol Meknatkhah; Alireza Imani; Parham Geramifar; Gholamhossein Riazi (Scientific Reports, 2023)
Abstract Extensive evidence highlights a robust connection between various forms of chronic stress and cardiovascular disease (CVD). In today's fast-paced world, with chronic stressors abound, CVD has emerged as a leading global cause of mortality. The intricate interplay of physical and psychological stressors triggers distinct neural networks within the brain, culminating in diverse health challenges. This study aims to discern the unique impacts of chronic physical and psychological stress on the cardiovascular system, unveiling their varying potencies in precipitating CVD. Twenty-one adolescent female rats were methodically assigned to three groups: (1) control (n = 7), (2) physical stress (n = 7), and (3) psychological stress (n = 7). Employing a two-compartment enclosure, stressors were administered to the experimental rats over five consecutive days, each session lasting 10 min. After a 1.5-month recovery period post-stress exposure, a trio of complementary techniques characterized by high specificity or high sensitivity were employed to meticulously evaluate CVD. Echocardiography and single-photon emission computed tomography (SPECT) were harnessed to scrutinize left ventricular architecture and myocardial viability, respectively. Subsequently, the rats were ethically sacrificed to facilitate heart removal, followed by immunohistochemistry staining targeting glial fibrillary acidic protein (GFAP). Rats subjected to psychological stress showed a wider range of significant cardiac issues compared to control rats. This included left ventricular hypertrophy [IVSd: 0.1968 ± 0.0163 vs. 0.1520 ± 0.0076, P < 0.05; LVPWd: 0.2877 ± 0.0333 vs. 0.1689 ± 0.0057, P < 0.01; LVPWs: 0.3180 ± 0.0382 vs. 0.2226 ± 0.0121, P < 0.05; LV-mass: 1.283 ± 0.0836 vs. 1.000 ± 0.0241, P < 0.01], myocardial ischemia [21.30% vs. 32.97%, P < 0.001], and neuroinflammation. This outcome underscores the imperative of prioritizing psychological well-being during adolescence, presenting a compelling avenue to curtail the prevalence of CVD in adulthood. Furthermore, extending such considerations to individuals grappling with CVD might prospectively enhance their overall quality of life.